Generation of a cellular model for mucopolysaccharidosis type IVA (MPS IVA) (AOUMEYi003-A) from a patient carrying compound heterozygous mutations p.G116V and p.G290S in the GALNS gene - Federica Feo; Silvia Falliano; Anna Caciotti; Marina Rinaldi; Alessia Caroli; Laura Giunti; Martino Calamai; Elena Procopio; Renzo Guerrini; Amelia Morrone; Rodolfo Tonin (Stem Cell Research)
Mucopolysaccharidosis type IVA (MPS IVA) is an autosomal recessive lysosomal storage disorder (LSD) caused by a deficiency of enzyme N-acetylgalactosamine-6-sulfatase (GALNS), characterised by systemic skeletal dysplasia and joint abnormalities with respiratory, cardiac and visceral manifestations. We generated a human induced pluripotent stem cell (hiPSC) line derived from MPS IVA patient’s fibroblasts. The patient was compound heterozygous for the known p.(Gly116Val) and p.(Gly290Ser) in the GALNS gene. We used a reprogramming RNA-based method. This hiPSC line was positive for “Yamanaka” factors and able to differentiate into all three germ layers, confirming its pluripotency potential.